MINAT BERWIRAUSAHA PESERTA PELATIHAN CAKE & COOKIES DI SANGGAR KEGIATAN BELAJAR(SKB) KABUPATEN GARUT - Saniati, Isyeu Siti (2015)
Penelitianinidilatarbelakangidengandiselenggarakannyapelatihan Tata BogaberbasiskewirausahaanyaituPelatihanCake danCookies di SanggarKegiatanBelajar (SKB) KabupatenGarut.Tujuandaripenelitianini, penulisinginmemperolehinformasiminatberwirausahapadapesertapelatihancake dancookies berdasarkanfaktor internal danfaktoreksternal.Metode yang digunakandalampenelitianiniadalahmetodedeskriptifdenganpopulasidansampel 30 orang. Hasilpenelitianmenunjukkanberdasarkanfaktor internal minatberwirausahasebesar 82% pesertamemilikiminatberwirausahasangattinggi, berdasarkanfaktoreksternalminatberwirausahasebesar 81% pesertamemilikiminatberwirausahasangattinggi. Simpulan, berdasarkanfaktor internal danekstenalminatberwirausahapesertapelatihancake dancookiesmemilikiminatberwirausahasangattinggi.Implikasidanrekomendasibagipanitiapenyelenggarapelatihancake dancookies agar membuat program pelatihanserupakarenadapatmenumbuhkanminatberwirausaha, dengantumbuhnyaminatberwirausahamakadapatmeningkatkanekonomimasyarakat. Kata Kunci :Minat, Berwirausaha, Pelatihan, Cake dan Cookies. This research is motivated by the convening of training Food & Culinary based entrepreneurial training Cake and Cookies in SanggarKegiatanBelajar (SKB) Garut. The purpose of this study the authors wanted to obtain information and description of entrepreneurship interest in trainees cake and cookies based on internal factors and external factors interest in entrepreneurship. The method used in this research is descriptive method with a population and a sample of 30 people. Results showed interest in entrepreneurship is based on an internal factor by 82% of participants have a very high interest in entrepreneurship. Results showed interest in entrepreneurship external factor by 81% of participants have a very high interest in entrepreneurship. In conclusion, based on internal factors and ekstenal interest in entrepreneurship trainees cake and cookies have a very high interest in entrepreneurship. Implications and recommendations for the training organizers cake and cookies in order to create a similar training program because it can foster interest in entrepreneurship, with the growing interest in entrepreneurship, it can improve the community economy. Keywords: Interest, Entrepreneurship, Training, Cake, Cookies